Revitalisasi, Sebuah Pendekatan Dalam Peremajaan Kawasan - Widjaja Martokusumo (Journal of Regional and City Planning, 2008)
Revitalisation is indeed an expression of institutionai policy as direct towards  the  structure  of  political  hegemony  and  economical  policy  of  a  certain  period  of  time. Sociocultural, environment and economic aspects have been the most important elements in creating sustainable environment. In essence, as a process revitalisation is an integrated effort to bring back the vitality  of  underused  and  deteriorated  urban  areas,  while  as  a  program  it  is  a  part  of  the  urban development  approaches.  This  paper  does  not  intend  to  differentiate  the  terminology  of  renewal, rehabilitation and gentrification, but rather tries to highlight the role and position of revitalization in conjunction with renewal process. As this paper argued, each of terminology has a specific characteristic in urban development. Discussion also highlights the problem of gentrification in urban development process, which might have negative impacts in urban revitalization process. The issue of civil society and people empowerment in urban revitalization have been raised in connection with the democratization of urban planning and development mechanism.